Sarcocystis neurona and related Sarcocystis spp. shed by opossums (Didelphis spp.) in South America - Pita Gondim, Luis Fernando (2021)
Protozoan parasites of the genus Sarcocystis are obligatory heteroxenous cyst-forming coccidia that infect a wide variety of animals and encompass approximately 200 described species. At least four Sarcocystis spp. (S. falcatula, S. neurona, S. lindsayi and S. speeri) use opossums (Didelphis spp.) as definitive hosts, and two of them, S. neurona and S. falcatula, are known to cause disease in horses and birds, respectively. Opossums are restricted to the Americas, but their distribution in the Americas is heterogeneous. Five Didelphis spp. are distributed in South America (D. aurita, D. albiventris, D. marsupialis, D. imperfecta and D. pernigra) whereas just one opossum species (D. virginiana) is found in North America. Studies conducted in the last decades show that Sarcocystis spp., derived from South American Didelphis spp., have biological and genetic differences in relation to Sarcocystis spp. shed by the North American opossum D. virginiana. The aim of this review was to address the peculiar scenario of Sarcocystis species shed by South American opossums, with a special focus on diagnosis, epidemiology, and animal infections, as well as the genetic characteristics of these parasites.